Enhanced waterlogging tolerance in barley by manipulation of expression of the N-end rule pathway E3 ligase PROTEOLYSIS6 - Mendiondo, Guillermina M.; Gibbs, Daniel J.; Szurman-Zubrzycka, Miriam; Korn, Arnd; Marquez, Julietta; Szarejko, Iwona; Maluszynski, Miroslaw; King, John; Axcell, Barry; Smart, Katherine; Corbineau, Francoise; Holdsworth, Michael J. (Wiley, 2015)
Increased tolerance of crops to low oxygen (hypoxia) during flooding is a key target for food security. In Arabidopsis thaliana (L.) Heynh., the N-end rule pathway of targeted proteolysis controls plant responses to hypoxia by regulating the stability of group VII ethylene response factor (ERFVII) transcription factors, controlled by the oxidation status of amino terminal (Nt)-cysteine (Cys). Here, we show that the barley (Hordeum vulgare L.) ERFVII BERF1 is a substrate of the N-end rule pathway in vitro. Furthermore, we show that Nt-Cys acts as a sensor for hypoxia in vivo, as the stability of the oxygen-sensor reporter protein MCGGAIL-GUS increased in waterlogged transgenic plants. Transgenic RNAi barley plants, with reduced expression of the N-end rule pathway N-recognin E3 ligase PROTEOLYSIS6 (HvPRT6), showed increased expression of hypoxia-associated genes and altered seed germination phenotypes. In addition, in response to waterlogging, transgenic plants showed sustained biomass, enhanced yield, retention of chlorophyll, and enhanced induction of hypoxia-related genes. HvPRT6 RNAi plants also showed reduced chlorophyll degradation in response to continued darkness, often associated with waterlogged conditions. Barley Targeting Induced Local Lesions IN Genomes (TILLING) lines, containing mutant alleles of HvPRT6, also showed increased expression of hypoxia-related genes and phenotypes similar to RNAi lines. We conclude that the N-end rule pathway represents an important target for plant breeding to enhance tolerance to waterlogging in barley and other cereals.